Organocatalytic route to the synthesis of (6S)-5,6-dihydro-6-[(2R)-2-hydroxy-6-phenylhexyl]-2H-pyran-2-one and ravensara lactones - Dwivedi, Namrata; Tripathi, Divya; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
An organocatalytic enantioselective synthesis of the title compounds has been achieved. The stereogenic centers were generated by the iterative use of proline catalyzed alpha-aminoxylations and HWE olefination of aldehydes while the lactone ring was constructed by ring closing metathesis. (C) 2011 Elsevier Ltd. All rights reserved.